Bilingualism Models: Do They Strengthen or Weaken the Oral Communicative Process in Contexts of English as a Foreign Language in Fifth Grade Primary Students? - Barón Ávila, Andrés (GIST – Education and Learning Research Journal, 2010)
This project presents a common and mistaken use of language that a group of fifth graders at a private bilingual school in Bogotá (Colombia) experienced at class time. In a common English as a foreign language (EFL) classroom situation which encompasses models of bilingualism that may be considered “difficulties,” the author proposes some strategies to improve the communicative oral process in English, avoiding code switching and code mixing in their speech. The present research is part of a proposal on class time reading and oral activities and its applicability is up to date due to the fact that it is based on current research-tested language strategies. I conclude that code switching and code mixing may be correlated to the student’s deficiency in target language competence, but I also conclude that if the activities focus on the three aspects of accuracy, rate, and prosody, students can experience an improvement in their communicative oral process. Likewise, it was observed that the use of the native language in the form of code switching can be accepted for the clarification of a message, but only in specific circumstances (as long as teachers do not let students use the language inappropriately). The present research is offered to scholarly communities to perhaps be organized into a workshop which may make language users aware of how to improve the linguistic, syntactic, and semantic usages of a second language.